Two new species of the genus Arboridia Zachvatkin from China (Hemiptera: Cicadellidae: Typhlocybinae) - Jiang, Jia; Luo, Gui-Mei; Song, Yue-Hua (Zootaxa, 2021)
Two new species of the leafhopper tribe Erythroneurini from Guizhou province, China, Arboridia (Arboridia) huajiangensis sp. nov. and Arboridia (Arborifera) changlingensis sp. nov. are described and illustrated. The ovipositor of A. huajiangensis sp. nov. is photographed and described. A key distinguishing all known species of the genus in China is provided.